Biomathematics in Paradoxes - Janos Vincze; Gabriella Vincze-Tiszay (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The three dimensional model of the sciences has the following five main layers: inorganic, organic, societal, mental, and spiritual. The biomathematics is a vertically connection between the first (inorganic) and second layers (organic). The marginal sciences are vertically and horizontally connected with the classical ones. The nature of the meeting points of heterogeneous sciences, the so called „border sciences” is that the appearance and rules are not based upon any of known classical scientific norms. The biomathematics is the result of the interaction at the borders of biology and mathematics. It is a result of a mathematical methodology which is connected directly to the biological sciences. Practically every mathematical procedure that is useful in physics, chemistry, engineering and economics has also found an important application in the life sciences.